Given data:
The given equation of the line is y= 2x/3 -3.
The standard equation of the line is,
![y=mx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/r9wr7tk2q8cfcans6j0owflua8au85op0h.png)
Compare the above equation with the given equation.
![m=(2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/25swg5xwadwmcmmbatdu5a1cpxdo71c95b.png)
The equation of the line perpendicular to the given line is,
![\begin{gathered} y-b=-(1)/(((2)/(3)))(x-a) \\ y-b=-(3)/(2)(x-a) \\ y=-(3)/(2)x+(3a)/(2)+b \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jj05bhto9k0d2rvfpxcbpefq7oidy55cu0.png)
Thus, the equation of the line perpendicular to the given line is y=-3x/2 +3a/2 +b.